An Unusual Case of Acute Traumatic Sequestrated Thoracic Disc Prolapse- a Case Report and Literature Review - Shen, Li; Ren, Wei; Xia, Qun; Lu, Jike (Archives of Clinical and Medical Case Reports, 2025)
Sequestrated thoracic disc herniation following a minor traumatic event without an apparent spinal fracture or dislocation is an extremely rare condition. Evaluation of a young morbid obese male with acute paraparesis secondary to an accidently sitting down to the floor revealed a right-sided extruded disc at the level of T7-8 and T8-9. At 12-month follow-up, he made a dramatic recovery following an appropriate surgical intervention. As soon as occurrence of acute paraparesis following a minor traumatic event, Magnetic Resonance Imaging (MRI) of the spine is necessary, even in the absence of radiological evidence of fracture-dislocation. Acute Thoracic Disk prolapse due to a traumatic injury is a relatively rare episode, especially in presence of neurological deficit after traumatic events, total spine MRI is appropriate, even in the absence of fracturedislocation in plain radiographs or total spine multi-directional CT scan. In the case of sequestrated thoracic disc herniation, transfacet pedicle-sparing approach is the preferred method for discectomy. A 29-years-old young morbidly obese man experienced acute paraplegia secondary to a falling down had a right-sided extruded disc at the levels of T7-8 and T8-9. After 12 months, he recovered very well after an appropriate discectomies. Following an acute paraparesis after a traumatic event without evidence of fracture-dislocation, thoracic MRI should be performed to rule out the possibility of epidural hematoma or a sequestrated disc